Is the information of systematic reviews published in nursing journals up-to-date? a cross-sectional study. Issue 1 (December 2017) - Tam, Wilson; Lo, Kenneth; Khalechelvam, Parames; Seah, Joey; Goh, Shawn
Abstract Background An up-to-date systematic review is important for researchers to decide whether to embark on new research or continue supporting ongoing studies. The aim of this study is to examine the time taken between the last search, submission, acceptance and publication dates of systematic reviews published in nursing journals. Methods Nursing journals indexed in Journal Citation Reports were first identified. Thereafter, systematic reviews published in these journals in 2014 were extracted from three databases. The quality of the systematic reviews were evaluated by the AMSTAR. The last search, submission, acceptance, online publication, full publication dates and other characteristics of the systematic reviews were recorded. The time taken between the five dates was then computed. Descriptive statistics were used to summarize the time differences; non-parametric statistics were used to examine the association between the time taken from the last search and full publication alongside other potential factors, including the funding support, submission during holiday periods, number of records retrieved from database, inclusion of meta-analysis, and quality of the review. Results A total of 107 nursing journals were included in this study, from which 1070 articles were identified through the database search. After screening for eligibility, 202 systematic reviews were included in the analysis. The quality of these reviews was low with the median score of 3 out of 11. A total of 172 (85.1%), 72 (35.6%), 153 (75.7%) and 149 (73.8%) systematic reviews provided their last search, submission, acceptance and online published dates respectively. The median numbers of days taken from the last search to acceptance and to full publication were, respectively, 393 (IQR: 212–609) and 669 (427–915) whereas that from submission to full publication was 365 (243–486). Moreover, the median number of days from the last search to submission and from submission to online publication were 167.5 (53.5–427) and 153 (92–212), respectively. No significant association were revealed between the time lag and those potential factors. Conclusion The median time from the last search to acceptance for systematic reviews published in nursing journals was 393 days. Readers for systematic reviews are advised to check the time taken from the last search date of the reviews in order to ensure that up-to-date evidence is consulted for effective clinical decision-making.